EDUKASI WAWASAN KEBANGSAAN MELALUI PELATIHAN DI BALAI DIKLAT KEAGAMAAN PALEMBANG - Musyaddad M.Si (Balai Diklat Keagamaan Jakarta, 2022)
Abstract The decline in national values caused by the absence of love for the country, lack of knowledge, and lack of education from a national perspective in some people become a big problem for the life of the nation and state. The information media that is widely open without boundaries is one of the factors causing the disappearance of the values of national insight. The purpose of this study is to find out how much understanding of the national insight of the trainees is and to educate the attitude of an ASN in understanding this national insight. This research was conducted with participants of the 1st generation of national insight training at the Palembang Religious Education and Training Center, totaling 35 respondents. The study used quantitative descriptive methods. Data were collected through observation, field notes, pretest, and posttest. The result of this study indicates that the result of increasing the understanding of training participants about national insight is “Very Good” in groups and individually. Seen from 35 training participants experienced an increase in both knowledge and attitudes. Abstrak Menurunnya nilai-nilai kebangsaan yang disebabkan dengan tidak adanya kasih sayang untuk negara, kurangnya pengetahuan dan kurangnya edukasi dalam berwawasan kebangsaan pada sebagian masyarakatmenjadi sebuah permasalahan besar bagi kehidupan berbangsa dan bernegara. Media informasi yang terbuka luas tanpa batas adalah salah satu faktor penyebab lunturnya nilai-nilai wawasan kebangsaan. Tujuanpenelitian ini adalah untuk mengetahui seberapa besar pemahaman wawasan kebangsaan peserta pelatihan dan mengedukasi bagaimana sikap seorang ASN dalam memahami wawasan kebangsaan ini. Penelitian ini dilakukan kepada peserta pelatihan wawasan kebangsaan angkatan 1 di Balai Diklat Keagamaan Palembang berjumlah 35 Responden. Penelitian menggunakan metode deskriptif kuantitatif. Data dikumpulkan melalui observasi, catatan lapangan, tes awal (pretest) dan test akhir (posttest). Hasil penelitian ini menunjukkan bahwa hasil peningkatan pemahaman peserta pelatihan tentang wawasankebangsaan “sangat baik” secara berkelompok maupun individu. Dilihat dari 35 Peserta Pelatihan mengalami peningkatan baik dalam pengetahuan dan sikap.